2023
DOI: 10.3390/plants12030662
|View full text |Cite
|
Sign up to set email alerts
|

Promising Bioregulators for Higher Water Productivity and Oil Quality of Chia under Deficit Irrigation in Semiarid Regions

Abstract: Appropriate water management practices are essential for the successful cultivation of chia in water-scarce situations of semiarid regions. This is highly essential when new crops such as chia are introduced for ensuring diversity and water saving. Therefore, field trials (2020–21 and 2021–22) were conducted to understand the impact of deficit irrigation and bioregulators (BRs) on the seed yield, water productivity, and oil quality of chia. The effect of foliar application of BRs such as thiourea (TU; 400 ppm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…Further, being a precursor of jasmonic acid, omega-3 must have been consumed in the stress-signaling process, as reported by Sánchez-Martín et al [52] under water stress. A possible association between high canopy temperature and more saturated fatty acids such as fatty acid deterioration was also reported [53] in soybean and chia crop [31]. The data generated in the present experiment suggest that chia + fenugreek intercropping can produce quality oil in terms of oil content in seeds and omega-3 as well as in chia monocropping (Table 4).…”
Section: Impact Of Water Deficit and Intercrop Competition On Quality...supporting
confidence: 76%
See 1 more Smart Citation
“…Further, being a precursor of jasmonic acid, omega-3 must have been consumed in the stress-signaling process, as reported by Sánchez-Martín et al [52] under water stress. A possible association between high canopy temperature and more saturated fatty acids such as fatty acid deterioration was also reported [53] in soybean and chia crop [31]. The data generated in the present experiment suggest that chia + fenugreek intercropping can produce quality oil in terms of oil content in seeds and omega-3 as well as in chia monocropping (Table 4).…”
Section: Impact Of Water Deficit and Intercrop Competition On Quality...supporting
confidence: 76%
“…Details of irrigation days, the actual quantity applied, and rainfall during the crop growth period are given in Table 1. Irrigation was applied to the crops treatment wise when CPE reached 100% and 50% of ETo equivalent, and irrigation time was calculated using the following formula [31].…”
Section: Irrigation Schedulingmentioning
confidence: 99%
“…Concerning the interaction effect between different foliar spray treatments and different water levels in Table ( Harisha et al, (2023) showed that deficit irrigation at 25, 50 and 75% ETo led to reductions in oil yield and in omega-3 yield in chia plant.…”
Section: Water Use Efficiency (Wue)mentioning
confidence: 99%